Apprendre à porter le regard sur les situations de travail : rôle des processus sémiotiques dans des espaces formatifs hybrides - Laurent Veillard; Jean-François Métral; Claire Masson (Activités)
Real farms and processing workshops within training establishments are a specific feature of secondary education in France in the field of agriculture and agri-food vocational education. They are considered to be more conducive to pedagogical accommodations than workplace learning. In particular, these training venues are designed to help students gradually learn to perceive and interpret the sign systems specific to different productive tasks. For novices, this semiotic dimension of professional activity is essential but relatively complex to learn. Ideally, they require mediation by expert trainers. In this paper, we present two case studies carried out in cheese and cured-meat production workshops in an agricultural college. We analyse the situated semiotic trajectories of a number of students and their trainers engaged in joint actions with a dual objective: production and training. Our results confirm the complexity of the semiotic processes involved. They also highlight how difficult it is for the trainers to exhaustively explain all the different types of knowledge (semiotic, scientific-technical and pragmatic) required to perceive and give meaning to the signs relating to the work to be carried out. In the concluding section, we suggest possible ways of improving the learning potential of these hybrid learning spaces, in particular the pivotal role that might be played by certain written supports such as production or quality monitoring sheets.